2005
DOI: 10.1073/pnas.0409394102
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared-emissive polymersomes: Self-assembled soft matter for in vivo optical imaging

Abstract: We demonstrate that synthetic soft materials can extend the utility of natural vesicles, from predominantly hydrophilic reservoirs to functional colloidal carriers that facilitate the biomedical application of large aqueous-insoluble compounds. Near-infrared (NIR)-emissive polymersomes (50-nm-to 50-m-diameter polymer vesicles) were generated through cooperative self assembly of amphiphilic diblock copolymers and conjugated multi(porphyrin)-based NIR fluorophores (NIRFs). When compared with natural vesicles com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
356
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 349 publications
(365 citation statements)
references
References 41 publications
5
356
0
3
Order By: Relevance
“…Although nanoparticles have been used with a spectrum of different imaging modalities including PET [48,49] and MRI [50][51][52], here we will focus on polymersomes that encapsulate fluorescent agents for optical imaging. Because light scattering decreases with increasing wavelength, and hemoglobin and water absorption spectra have their nadir in the near infrared (NIR) spectral region, much work has been focused on developing NIR contrast agents for in vivo imaging studies [9]. To this end, Ghoroghchian et al have successfully loaded porphyrinbased near infrared fluorophores (NIRFs) into the hydrophobic bilayer membranes of PEO-b-PBD [9,10,53,54], PEO-b-PCL [54], PEO-b-PEE [54], and poly(ethylene oxide)-block-poly (methylcaprolactone) (PEO-bPmCL) [54] polymersomes.…”
Section: Diagnostic Applications Of Polymersomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although nanoparticles have been used with a spectrum of different imaging modalities including PET [48,49] and MRI [50][51][52], here we will focus on polymersomes that encapsulate fluorescent agents for optical imaging. Because light scattering decreases with increasing wavelength, and hemoglobin and water absorption spectra have their nadir in the near infrared (NIR) spectral region, much work has been focused on developing NIR contrast agents for in vivo imaging studies [9]. To this end, Ghoroghchian et al have successfully loaded porphyrinbased near infrared fluorophores (NIRFs) into the hydrophobic bilayer membranes of PEO-b-PBD [9,10,53,54], PEO-b-PCL [54], PEO-b-PEE [54], and poly(ethylene oxide)-block-poly (methylcaprolactone) (PEO-bPmCL) [54] polymersomes.…”
Section: Diagnostic Applications Of Polymersomesmentioning
confidence: 99%
“…Studies using PEO-b-PBD polymersomes have shown that porphyrin-based NIRFs, when encapsulated in polymersomes, are able to generate a signal with enough intensity to penetrate through 1 cm of a solid tumor [9]. Further, when these NIR-emissive nanopolymersomes are injected into the tail-vein of mice, the biodistribution of the nanoparticles can be tracked in vivo via non-invasive NIR fluorescence-based optical imaging [55].…”
Section: Diagnostic Applications Of Polymersomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 40 mg of NaBH 4 , 60 mg of tellurium powder and 3.0 mL of H 2 O were added into a small flask in sequence and then the flask was put in a 40 • C water bath. The reacting system was stirred under the protection of N 2 and the black tellurium powder disappeared after 1 h, obtaining a clear purple NaHTe solution.…”
Section: Synthesis Of Cdhgte/gelatin Nanospheresmentioning
confidence: 99%
“…Based on this unique deeper tissue-penetrative property as well as non-ionizing and non-radioactive advantages, the research of NIR non-invasive imaging techniques attracted extensive attentions for real time and dynamic monitoring/tracing of biological signals in living animals. As a newly emerged optical technique, NIR imaging was successfully applied in many frontier fields of life sciences, such as nanomedicine research [3,4], cancer diagnosis and treatment [5,6] in recent years.…”
Section: Introductionmentioning
confidence: 99%